ANALYSIS OF THE LEVEL OF E-GOVERNMENT IN THE PUBLIC ADMINISTRATION IN OUR COUNTRY - ANCA JARMILA GUŢĂ (Annals of the University of Petrosani: Economics)
The paper presents the stage of e-government in the field of public administration in our country, presenting the level of e-government compared to that of other EU states. Changes in technology have led to changes in the structure and activity of organisations, and in particular, a public institution, for which e-government practices and technologies have become increasingly important for all types of organizations, but especially for public administrations that need to offer citizens the benefits of e-government in order to support the most effective interaction between citizens and the public institutions with which they interact. In this context, the path of a public institution towards greater efficiency goes through a permanent management of the e-government instruments it uses both in its internal and external activity in order to improve and improve its.